Related and Unrelated Diversification, Impact of Intergeneration in Family Firms Performance: Narrative Literature Review in Family Business Context: English - Widayanti, Rochmi; Setiawan; Muhammad Firdaus, Rifqi (Indonesian Journal of Economics and Management, 2025)
This narrative literature review aims to critically review the development of research on diversification policies and company performance in the context of family company ownership in Asian countries. The study is based on a review of 75 empirical research articles. The findings from the review state that there are still inconsistencies in research results in improving performance. The diversification policies that are related and non-related give mixed results on increased performance and corporate excess value. Motivation of family companies in developing diversified businesses is interpreted differently according to agency theory, resources-based theory, and social wealth theory. The role of the pyramid ownership structure and the transformation between generations of families also contributes to determining the impact of diversification on improving company performance. This study recommends future research to develop a more holistic understanding of the determinant and contextual models in differentiating the performance of family firms in determining related and non-related diversification policy choices. Keyword: ownership structure, diversification, family firm performance